2021
DOI: 10.4103/jfmpc.jfmpc_1627_20
|View full text |Cite
|
Sign up to set email alerts
|

Bukuryoingohangekobokuto may improve recurrent aspiration pneumonia in patients with brain damage and reduce the caregiver burden

Abstract: A 17-year-old girl with hypoxic encephalopathy was hospitalized over four times in a year because of recurrent aspiration pneumonia (AP). She had dysphagia and reduced cough reflex as sequelae of brain damage. To prevent aspiration, a gastric tube was placed for feeding, but it did not reduce the frequency of AP because the gastroesophageal reflux caused backflow. However, after the Kampo medicine bukuryoingohangekobokuto (BRIHK) was added to the prescriptions, her sputum and gastroesophageal reflux was remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…We previously reported that BRGHT could inhibit corticotropin-releasing hormone receptor 2, dopamine receptors D2 and D3, neuropeptide Y receptor type 2, and acetylcholinesterase, which synergistically improves gastric emptying ( Mogami et al, 2020 ). BRGHT administration also reduces the frequency of aspiration pneumonia in patients with brain damage ( Takayama et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that BRGHT could inhibit corticotropin-releasing hormone receptor 2, dopamine receptors D2 and D3, neuropeptide Y receptor type 2, and acetylcholinesterase, which synergistically improves gastric emptying ( Mogami et al, 2020 ). BRGHT administration also reduces the frequency of aspiration pneumonia in patients with brain damage ( Takayama et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%